Construction of a high-density adzuki bean genetic map and evaluation of its utility based on a QTL analysis of seed size - Li-xia WANG; Jie WANG; Gao-ling LUO; Xing-xing YUAN; Dan GONG; Liang-liang HU; Suhua WANG; Hong-lin CHEN; Xin CHEN; Xu-zhen CHENG (Journal of Integrative Agriculture, 2021)
Adzuki bean (Vigna angularis (Willd.) Ohwi & Ohashi) is an annual cultivated leguminous crop commonly grown in Asia and consumed worldwide. However, there has been limited research regarding adzuki bean genetics, which has prevented the efficient application of genes during breeding. In the present study, we constructed a high-density genetic map based on whole genome re-sequencing technology and validated its utility by mining QTLs related to seed size. Moreover, we analyzed the sequences flanking insertions/deletions (InDels) to develop a set of PCR-based markers useful for characterizing adzuki bean genetics. A total of 2904 markers were mapped to 11 linkage groups (LGs). The total length of the map was 1365.0 cM, with an average distance between markers of 0.47 cM. Among the LGs, the number of markers ranged from 208 (LG7) to 397 (LG1) and the total distance ranged from 97.4 cM (LG9) to 155.6 cM (LG1). Twelve QTLs related to seed size were identified using the constructed map. The two major QTLs in LG2 and LG9 explained 22.1 and 18.8% of the total phenotypic variation, respectively. Ten minor QTLs in LG4, LG5 and LG6 explained 3.0–10.4% of the total phenotypic variation. A total of 9718 primer pairs were designed based on the sequences flanking InDels. Among the 200 selected primer pairs, 75 revealed polymorphisms in 24 adzuki bean germplasms. The genetic map constructed in this study will be useful for screening genes related to other traits. Furthermore, the QTL analysis of seed size and the novel markers described herein may be relevant for future molecular investigations of adzuki bean and will be useful for exploiting the mechanisms underlying legume seed development.